OP06 Creating a foundation 'simulation champion' role. (July 2019) - Baxter, Lucy; Panter, Simon; Jachuck, Mickey
Abstract : Aim: To provide Foundation trainees with opportunities to develop their skills in medical education, clinical governance and leadership. To provide Foundation trainees with access to simulation faculty training. To encourage junior doctors to take on roles in medical education in their future careers. To provide faculty support for the simulation courses at South Tyneside District Hospital. To identify areas where simulation can improve patient care and complete quality improvement cycles within these. Objectives: F1 doctors (first year post qualification) were recruited in April to be a 'Simulation Champion' in their F2 year. Of 26 doctors, 9 applied and were appointed. The role is supported by the Simulation Fellow. Following an initial meeting with the Simulation Fellow, the following agreements were established. The Foundation Simulation Champions will: promote simulation within the trust. assist with preparation and delivery of simulation (minimum 3 days commitment). complete a QI (quality improvement) project (full cycle) within simulation. The Simulation Fellow will: support and assist the Foundation Champions with their QI projects. provide simulation training and promote any regional training opportunities to the Foundation Champions. give feedback on teaching and debriefing skills. provide certificates and letters of reference. Summary of work undertaken: The Simulation Champions' help with simulation has been invaluable in allowing the smooth running of all courses to date. They have collectively totalled over 50% of the faculty on courses this year and have contributed to the scenario bank. Through their enthusiasm, other junior doctors have come forward to help with faculty as well. In three small groups, the Simulation Champions have completed QI projects: 'Acute Scenarios Simulation for Foundation Doctors', 'Using Simulation to Improve ACS (acute coronary syndrome) Management' and 'Multidisciplinary Simulation to Improve Confidence in Communicating in Difficult Scenarios'. All three of these projects have been very successful and have been presented regionally and nationally. Impact on practice: The Foundation Simulation role has allowed Foundation Doctors to develop their teaching and organisational skills. It has also given them a chance to develop skills in clinical governance, specifically audit and quality improvement. Through their QI projects they have developed a simulation programme to improve communication where 100% of attendees reported an increase in confidence, they have measured changes to practice reported by Foundation Doctors following acute scenario simulation, and they have developed and promoted a new ACS protocol to improve patient outcomes. The current Simulation Champions will recruit the next cohort and support them in the initial stages of a QI project. The role is therefore self-sufficient even when the current Simulation Fellow is no longer in role. All Foundation Simulation Champions this year have been successful in their job interviews to date with three entering teaching fellow roles, two entering GP training, one working as an ultrasound and simulation fellow, one being a clinical fellow and two as yet undecided. Overall the role has been a great success in recognising and encouraging junior doctors' invaluable contributions to medical education and patient care, as well as proving a cost-free method of boosting faculty numbers for simulation courses.